Modeling of multiple crack initiation in polymer pipes under oxidative environment. (1st June 2022) - Wee, Jung-Wook; Chudnovsky, Alexander; Choi, Byoung-Ho
Highlights: A novel fundamental model for the multiple crack initiation behavior of polymer pipes transporting oxidative fluids was proposed. Green's function for the stress intensity factor of various crack numbers, sizes, and standard dimension ratios was developed. The number of crack initiations and durations were successfully simulated using potential energy analysis with SCCs. Abstract: In this study, a novel fundamental model for the multiple crack initiation behavior of polymer pipes transporting fluids with strong oxidizing agents was proposed. Because the oxidant diffuses into the polymer medium with consumption by oxidation, a volumetric sink of the diffused oxidant was considered. The degradation kinetics of the polymer pipes were modeled by diffusion using the reaction equations. To compare the released energy with the crack initiation, Green's function for the stress intensity factor of various crack numbers, sizes, and standard dimension ratios (SDRs) was developed. The number of crack initiations and durations were successfully simulated using potential energy analysis with cracking. At a relatively low internal pressure in an oxidative environment, multiple cracks were estimated with a proper scale of the crack length. Instead, it was predicted that one main crack would be initiated at a higher level of internal pressure. In addition, the knee points representing the slope change of the internal pressure-lifetime plot were shown between these different failure modes, in agreement with previous observations. The experimental results of sustained hydrostatic pressure tests of polymer pipes under chlorinated water can be accurately simulated by the proposed model.